Tembang Macapat Sebagai Metode Untuk Penanaman Dasar-Dasar Musikalitas - Wahyudiono, Teguh; Mulyanto, Mulyanto; Supriyadi, Slamet (Resital: Jurnal Seni Pertunjukan, 2022)
ABSTRACT This research departs from a problem, namely that students of the Mangkunegaran Art Academy in Surakarta the II semester for the academic year 2021/2022 have difficulty understanding the musicality of the tembang macapat which includes titilaras and laya. Thus, this study aims to describe the learning process of the tembang macapat as an inculcation of the basics of student musicality in the students of the karawitan arts study program at the Mangkunegaran Art Academy in Surakarta. Researchers examine learning from the learning stages (pre, process, and post), learning components (objectives, materials, models, methods, media, and evaluation) and the basics of musicality including titilaras and laya. The research subjects are II semester students for the 2020/2021 academic year. The researcher chose a qualitative method in descriptive form by engaging directly with students and lecturers during the research process to obtain information and data about the learning process. The results of this study prove that there is an influence of the tembang macapat learning process on the cultivation of the basics of musicality in the form of theory and practice. This can be seen from the success of lecturers in instilling the basics of musicality to students as evidenced by 81.25% of students when presenting tembang macapat well in emphasizing titilaras and laya, due to various factors, namely basic conditions and student skills (eg the sound of sasap, blero, false "does not match the tone notation" and the beat of each tembang macapat is not the same), there are still 18.75% of students who have not been able to present the tembang macapat according to the predetermined titilaras and laya. According to the research findings, it can be said that lecturers have succeeded in carrying out their obligations as competent educators, apply learning tools well and are able to form creative, disciplined, independent, and motivated students.ABSTRAK Penelitian ini berangkat dari sebuah permasalahan yaitu mahasiswa Akademi Seni Mangkunegaran Surakarta pada semester II tahun ajaran 2020/2021 mengalami kesulitan dalam memahami tentang musikalitas tembang macapat yang diantaranya titilaras dan laya. Sehingga penelitian ini bertujuan untuk mendeskripsikan proses pembelajaran tembang macapat sebagai penanaman dasar-dasar musikalitas mahasiswa di progam studi seni karawitan Akademi Seni Mangkunegaran Surakarta. Peneliti mengkaji pembelajaran dari tahapan pembelajaran (pra, proses, dan post), komponen pembelajaran (tujuan, materi, model, metode, media, dan evaluasi) dan dasar-dasar musikalitas diantaranya titilaras dan laya. Subjek penelitian adalah mahasiswa semester II tahun ajaran 2020/2021. Peneliti memilih metode kualitatif dalam bentuk deskriptif dengan melakukan keterlibatan langsung dengan mahasiswa dan dosen selama proses penelitian untuk mendapatkan informasi dan data tentang proses pembelajaran. Hasil penelitian ini membuktikan bawa adanya pengaruh proses pembelajaran tembang macapat terhadap penanaman dasar-dasar musikalitas dalam bentuk teori maupun praktik. Hal ini dapat dilihat dari keberhasilan dosen dalam menamkan dasar-dasar musikalitas kepada mahasiswa dengan dibuktikan 81,25% mahasiswa ketika menyajikan tembang macapat dengan baik dalam penekanan titilaras dan laya, karena berbagai faktor yaitu kondisi dasar dan keterampilan mahasiswa (misal suara sasap, blero, fals “tidak sesuai notasi nada” dan ketukan setiap tembang macapat tidak sama), masih ada 18,75% mahasiswa yang belum bisa menyajikan tembang macapat sesuai dengan titilaras dan laya yang sudah ditentukan. Menurut temuan penelitian sehingga bisa dikatakan yakni dosen telah berhasil melaksanakan kewajibannya sebagai tenaga pendidik yang berkompeten, menerapkan perangkat pembelajaran dengan baik dan mampu membentuk mahasiswa yang kreatif, dispilin, mandiri, dan memiliki motivasi.